EFEKTIVITAS PELAKSANAAN SUPERVISI AKADEMIK DALAM MENGOPTIMALKAN KINERJA GURU DALAM MENYUSUN DAN MELAKSANAKAN RPP AKADEMIK BERKELANJUTAN DI SDN 1 NGUDIKAN - Suprihatin, Ninik (Jurnal Muassis Pendidikan Dasar, 2023)
Purpose the research objective was to improve teacher performance in compiling complete learning tools through continuous academic supervision at SD Negeri 01 Ngudikan, Wilangan District, Nganjuk Regency. Specifically, this study aims to find out the appropriate steps in carrying out continuous academic supervision so as to be able to improve teacher performance in preparing and implementing lesson plans at SD Negeri 01 Ngudikan for the 2016/2017 academic year. This research is a school action research (PTS). Using 2 cycles, the first cycle is to determine teacher performance in preparing lesson plans and learning, and cycle 2 to perfect the results of cycle 1. The results of this study are through academic supervision in optimizing teacher performance in preparing lesson plans and learning are: teacher performance in preparing lesson plans (RPP) in cycle I, the average was only 62.3%, in cycle II there was an increase to 82.3%. This means that there was an increase of 22%. the average of 62.5% in cycle II increased to 84.51% meaning there was an increase of 22.1%. In this case, it means that through continuous academic supervision it can improve teacher performance in compiling and implementing lesson plans in SDN 01 Ngudikan 01, Wilangan District, Nganjuk Regency semester II of the 2016/2017 academic year.